Research on the automatically trajectory control of a spherical isolation plug in subsea pipeline - Zhu, Xiaoxiao; Wang, Hao; Li, Fengqin; Quan, Yi; Wang, Wenming; Zhang, Shimin (Ocean engineering, 2017)
The rapid growth demanding for oil and gas resources has gradually driven the fossil energy exploitation from the land to the ocean. Technology shifts from manually operated oil fields to the remotely operated oil fields is necessary, and robotic assistance to human cognition is essential. Hot tapping and line stop techniques, as a great method for the replacement of the risky pipelines without disrupting the service to customers, demands for the automation to improve the efficiency and reliability. In this paper, automatically trajectory control of a spherical isolation plug in subsea pipeline was investigated. Mathematical model for the spherical plug head insertion was presented, and two control algorithms for the automatically insertion of the plug were proposed, named the rotation angle based control algorithm and the vertical displacement based control algorithm. Simulation was conducted and the results indicate that the vertical displacement based control algorithm owes better performance than the rotation angle based control algorithm. The accuracy and efficiency of the vertical displacement based control algorithm was then experimentally researched. The results in this paper can provide references for the automatically trajectory control of an isolation plug, as well as improve the accuracy and reliability of offshore hot tapping. •Automatically trajectory control of a spherical isolation plug was investigated.•Two control algorithms for the control of the spherical plug head were proposed.•The performance of these two algorithms were compared and verified by experiments.